Catheter ablation for atrial fibrillation. Issue 1 (16th December 2004) - Jais, P; Sanders, P; Hsu, L F; Hocini, M; Haissaguerre, M
Abstract : Recent advancements in our understanding of atrial fibrillation have led to the development of catheter ablation techniques that feasibly could achieve a cure for AF